Haji Mutamakin Dan Cerita Dewa Ruci Dalam Serat Cebolek (Relasi Sosial-Budaya Dan Keagamaan Dalam Kacamata Fenomenologi Edmund Husserl) - Abdul Rosyid (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2021)
Serat Cebolek as a classic literary work is authentic evidence of the religious conflict between Haji Mutamakkin and Ketib Anom Kudus which is motivated by different perspectives on Islam. There is an imbalance in describing the two figures. Haji Mutamakkin, who tended to be cornered in court, seemed to have deviated and left Islam in preaching on the pretext of using the Dewa Ruci’s story as his medium. In this context, there is a need for historical rectification, what Yasadipura I described about Haji Mutamakkin is not in accordance with social facts. Phenomenology as a problem analysis tries to see two sides, namely the text of Serat Cebolek and existing socio-cultural phenomena. Dewa Ruci's story as a cultural trend of Javanese society became the prima donna which was later supported by wayang as a folk performance art. Coupled with the existence of a spiritual relationship in the analogy of Islamic teaching. Of course this has had a positive impact on the development of Islam in Java, especially in Pantura’s society (Pantai Utara). Islam develops humanistly without eliminating existing culture.